2020
DOI: 10.1029/2019ja027713
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Electron Precipitation During Pulsating Aurora and Its Chemical Impact

Abstract: Pulsating auroras (PsAs) are low-intensity diffuse aurora, which switch on and off with a quasiperiodic oscillation period from a few seconds to ∼10 s. They are predominantly observed after magnetic midnight, during the recovery phase of substorms and at the equatorward boundary of the auroral oval. PsAs are caused by precipitating energetic electrons, which span a wide range of energies between tens and hundreds of keV. Such energetic PsA electrons will deposit their energy at mesospheric altitudes and induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 59 publications
6
42
1
Order By: Relevance
“…It is also possible to find cases where energies of APA electrons are higher than those of PPA electrons, specifically in the energy range below the energy limit (30 keV) measured by FAST. The stopping altitude of these electrons is above 95 km (Turunen et al, 2009). However, in this study, most of the energy (ionization) differences between the types were observed below 100 km.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It is also possible to find cases where energies of APA electrons are higher than those of PPA electrons, specifically in the energy range below the energy limit (30 keV) measured by FAST. The stopping altitude of these electrons is above 95 km (Turunen et al, 2009). However, in this study, most of the energy (ionization) differences between the types were observed below 100 km.…”
Section: Discussioncontrasting
confidence: 53%
“…They further indicated that the intense ionization could lead to a significant effect on the ionospheric conductivity and current system and, in turn, affect the motion and shapes of PsA patches. Hard precipitation of PsA electrons is known to reach below 70 km and can ionize and change the chemistry of the mesosphere (Turunen et al, 2009(Turunen et al, , 2016Tesema et al, 2020). It has also been shown by model results that not all PsA electrons cause strong ionization and chemical changes (Tesema et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The energetic electron precipitation (EEP) that produces PsA is thought to arise from chorus wave activity, whereby electrons from the radiation belts are scattered into the atmospheric loss cone (Thorne et al, 2010;Kasahara et al, 2018). The precipitating electrons typically have energies up to the order of 10-100 keV, depositing their energy into the upper mesosphere/lower thermosphere region at approximately 70-120 km altitude (Fang et al, 2008;Turunen et al, 2009;Miyoshi et al, 2010;Tesema et al, 2020b). PsA-related electron density enhancements have been observed at altitudes as low as 68 km, corresponding to electron energies of at least 200 keV (Miyoshi et al, 2015;Turunen et al, 2016;Tesema et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ionization in the D region leads to enhanced absorption of the cosmic noise, and at D-region heights this is mainly due to precipitation of electrons with energies above 10 keV (e.g. Turunen et al, 2009). The SGO riometers are wide-beam instruments which listen to the cosmic noise at approximately 30 MHz.…”
Section: From Cosmic Noise Absorption To a Regional Absorption Indexmentioning
confidence: 99%
“…The one-dimensional Sondakylä Ion and Neutral Chemistry model (e.g. Turunen et al, 2009) was run to investigate the production of odd hydrogen (HO x = OH+HO 2 ) and odd nitrogen (NO x = N+NO+NO 2 ) due to the strong ionization at the bottom part of the ionosphere and the following catalytic depletion of mesospheric ozone. The peak loss of mesospheric ozone was found to be 10 %-50 % depending on the season.…”
Section: Introductionmentioning
confidence: 99%